Pre-6G Graduate Education of Communications Engineering - Dang, Shuping; Alouini, Mohamed-Slim; Shihada, Basem (Frontiers in Communications and Networks, 2022)
As sixth-generation (6G) communications have been widely discussed in the past two years, it is now the right time to investigate the potential impacts of 6G communications on the current graduate education system of communications engineering. In this article, we articulate a set of existing problems with the graduation education of communications engineering and analyze the trends and challenges of pre-6G graduate education of communications engineering. By this article, we not only aim to diagnose the existing problems with corresponding trends and challenges but also to call for proactive measures coping with them. Besides, we would also like to use this article to encourage more and more brave undergraduates to participate in communications engineering, a fast-changing and far-reaching discipline.